Hubungan Tingkat Ekonomi Keluarga Dengan Kejadian Stunting Di Kecamatan Long Ikis Kabupaten Paser (Jurnal Fenomena Kesehatan, 2025)
Stunting or chronic malnutrition is another form of growth failure that arises as a result of long-standing malnutrition. This study aims to determine the relationship between family economic level and the incidence of stunting in Long Ikis District, Paser Regency in 2022. This research is a quantitative type through a cross sectional approach with the sampling technique used is non-probability sampling with purposive sampling type with a total sample of 49 people. The results showed that respondents with a family economic level relationship with the incidence of stunting showed that respondents with a low economy were 1 person (2.0%) with good knowledge of stunting 0 and with less knowledge of stunting as many as 1 person (2.0%), while respondents with moderate economy as many as 31 people (63.3%) with good knowledge of stunting 26 people (53.1%) and with less knowledge of stunting 5 people (10.2%). And in the high economy as many as 17 people (34.7%) with good knowledge of stunting as many as 15 people (30.7%) and with less knowledge of stunting 2 people (4.1%). The results of the Chi-Square test showed that there was no relationship between family economic level and the incidence of stunting in Long Ikis District, Paser Regency with p = 0.068